PROBLEMS OF ENGLISH TEACHING LEARNING IN MULTICULTURAL CLASSROOM IN STMIK BUMIGORA MATARAM - Miswaty, Titik Ceriyani (IKIP Mataram, 2017)
This study deals with teaching learning English in multicultural classroom in STMIK Bumigora Mataram and aims at investigating what problems that obstruct students in learning English in the classrooms. In order to find the answer of research problems, this study useddescriptive qualitative methods in which some tools as questioner and interview were used as data instruments to collect the data. The subject of this study is students from four English classes in STMIK Bumigora Mataram who come from some tribes in Indonesia and 2 lectures that teach in those classes. The findings of this study are problems there are some problems such as; 1) Syllabus which used is not well prepared, 2) the material that is used is not suitable with the needs of students, and 3) dialect of students? mother tongue. After findingthe problems that happen in multicultural classrooms in STMIK Bumigora Mataram.